2011
DOI: 10.1902/jop.2011.110031
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin Enhances the Proliferation of Cementoblast Lineage Cells

Abstract: The results show that rh174 interacts with CD63, and rh174/CD63 interaction activates the ERK1/2 signaling pathway, enhancing the proliferation activities of HCEM and HPDL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Haze, 2009 [8]; Tamburstuen, 2011 [10], 2. Zeichner-David, 2006 [57]; Fukae, 2006 [58]; Matsuzawa, 2009 [59]; Tambursten, 2010 [42]; Kakegawa, 2010 [60]; Zhang, 2011 [54]; Kitagawa, 2011 [53]; Kunimatsu, 2011 [61]; Izumikawa, 2012 [62]; Amin, 2013 [63], 3. Spahr, 2006 [36]; Haze, 2009 [8]; Iizuka, 2011 [18]; Tamburstuen, 2011 [10]; Atsawasuwan, 2013 [40], 4.…”
Section: Discussionmentioning
confidence: 99%
“…Haze, 2009 [8]; Tamburstuen, 2011 [10], 2. Zeichner-David, 2006 [57]; Fukae, 2006 [58]; Matsuzawa, 2009 [59]; Tambursten, 2010 [42]; Kakegawa, 2010 [60]; Zhang, 2011 [54]; Kitagawa, 2011 [53]; Kunimatsu, 2011 [61]; Izumikawa, 2012 [62]; Amin, 2013 [63], 3. Spahr, 2006 [36]; Haze, 2009 [8]; Iizuka, 2011 [18]; Tamburstuen, 2011 [10]; Atsawasuwan, 2013 [40], 4.…”
Section: Discussionmentioning
confidence: 99%
“…Amelogenin protein, such as rp(H)M180, has recently been shown to enhance the growth rate for human PDL cells and BMSCs [23, 44, 45]. Samples containing more CD146 marked cells respond by proliferation not only to rp(H)M180, but to all mitogens tested [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that recombinant full-length amelogenin (rh174 or rm180) binds to LAMP-1 or LAMP-3 expressed on the cell membrane of cementoblasts 21,25) , and that the presence of LAMP-3 antibody in the culture medium inhibited the cementoblast proliferation promoted by rh174 25) . Furthermore in cementoblast, LRAP showed no effect on cell proliferation 36) .…”
Section: Discussionmentioning
confidence: 99%
“…ATDC5 and MC3T3-E1 cells were seeded at 1 × 10 3 cells per well on a 96-well plate, and after 3 hours for initial cell attachment, the serumfree growth medium was changed to media with or without 10 g/ml of LRAP. For the inhibition experiment, the medium was changed to contain both LRAP and rat monoclonal antibody to mouse LAMP-1 (Santa Cruz Biotech, Tokyo, Japan) diluted to 2 g/ml according to a previous report 25) . After 48 hours of culture, the cells were incubated with the counting reagent for one hour as per the manufacturer's instructions.…”
Section: Cell Proliferationmentioning
confidence: 99%